Adjustment and Adaptation of Female International Higher Education Students: A Qualitative Study - Mercan, Zeynep (Border Crossing, 2024)
Deciding to be an international student is challenging, and adjusting to a new culture is even more so for women from collectivistic cultures. Despite some attention to women’s adjustment and adaptation to different cultures, limited attention has been given to the specific challenges faced by women from diverse collectivistic backgrounds. This qualitative study explored the cultural adaptation experiences of 5 Chinese, 2 Azerbaijani, and 3 Turkish international master’s students through semi-structured interviews. Using the thematic approach, four main themes emerged from the data regarding how female students adjust to the new culture: educational adaptation, formation of social groups and language learning, understanding identity and gender, and emotional involvement in the new culture and future planning. The implications for psychological well-being and future career decisions are discussed in detail.